Dampak Inklusi Keuangan Digital Terhadap Perilaku Konsumsi Rumah Tangga Di Indonesia: Analisis Berbasis Gender - Alya Putri; Maizul Rahmizal (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to determine the extent of the impact of digital financial inclusion on household consumption behavior in Indonesia and the extent of its influence when interacted with gender. This study uses secondary data sourced from the National Social and Economic Survey (SUSENAS) by the BPS-Statistics Indonesia in 2025 in Indonesia and this study uses quantile regression analysis. The dependent variable of this study is household consumption, the independent variable is digital financial inclusion, the interaction variable is the gender of the head of the household, the control variables are the characteristics of the head of the household and demographic characteristics. The results of the study indicate that (1) The digital financial inclusion variable has a positive and significant effect on household consumption (2) The impact of digital financial inclusion on consumption expenditure in households with female heads of households is smaller than in households with male heads of households. Based on this, the researcher recommends that the government increase digital financial inclusion and financial literacy, especially in communities with low education levels and low incomes, and empower women to eliminate barriers to access and utilization of digital financial inclusion.